IMPLEMENTASI SEASONAL AUTOREGRESSIVE INTEGRATED MOVING AVERAGE DALAM PERAMALAN PRODUKSI DAN KONSUMSI BERAS DI PROVINSI NUSA TENGGARA TIMUR TAHUN 2025-2027 - Agatha Herdiani Bria (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
Food self-sufficiency is a priority in the current government's program, including for the provincial government of East Nusa Tenggara (NTT). According to BPS data, during 2018-2024, domestic rice production was unable to meet the consumption needs of the people of NTT, despite various efforts made by the government. This research aims to forecast rice and paddy production, as well as its sufficiency in meeting the consumption needs of the NTT community for the period 2025-2027. The data used is monthly data on rice production, rice production, and rice consumption for the period 2018-2024. The forecasting methods used are seasonal ARIMA (5,1,4)(1,1,0)12 for rice production and (3,1,3)(1,1,1)12 for rice consumption, while rice production is calculated using the results of the 2018 Grain-to-Rice Conversion Survey (SKGB) and the 2018-2020 NBM grain/rice loss/spillage conversion against rice production. The forecasting results show that rice production and consumption needs are not yet met, while in 2027, rice will experience an aggregate surplus.